Perspektif Asset Pricing Model dan Pengembangannya Pada Pasar Modal Indonesia - Yunan Surono; Akhmad Irwansyah Siregar; R Adisetiawan (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Every investor will pay attention to return and risk in investing in portfolios. In portfolio investment, this is known as the principle of high return high risk. To see this return and risk, 4 (four) models are known, namely 1) Capital Asset Pricing Model (CAPM) with beta factors (market risk), 2) French Fama models with beta, size and value factors, 3) Carhart model with factors beta, size, value and momentum, 4) the Arbitrage Pricing Theory (APT) model in this study, in addition to factors such as the model above, macro economic factors include economic growth, inflation, interest rates, the rupiah exchange rate against US dollars and the money supply. Models 1, 2 and 3 analyze from the fundamental side of the company while models 4 analyze from the macroeconomic side. Based on the theory of Ying (1966), Tauchen & Pitts (1983), Blume (1994), Lee & Swaminathan (2000), Gervais (2001) and Kaniel (2003) that the total trading volume affects the movement of stock indexes, stock prices and affects the magnitude of the level return and investment risk, then in this study the researchers added the total volume of activity factor as an effort to overcome the weaknesses found in the Carhart model where in calculations using the three sequential sort method, this model has not been able to record a holding period (the length of shares in the hands of investors) which in this study. The model with the addition of the total volume activity variable as a five factor pricing model is a model of the researcher's development. From the test results it can be concluded that the development model turned out to be better precision in estimating return and risk and its accuracy is more accurate than existing models.